2016
DOI: 10.1159/000453211
|View full text |Cite
|
Sign up to set email alerts
|

Is Overexpression of Ki-67 a Prognostic Biomarker of Upper Tract Urinary Carcinoma? A Retrospective Cohort Study and Meta-Analysis

Abstract: Background: Upper tract urinary carcinoma (UTUC) is a relatively uncommon but aggressive disease. The Ki-67 antigen is a classic marker of cellular proliferation, but there is still controversy regarding the significance and importance of Ki-67 in tumor progression. Methods: In this study, we first detected Ki-67 expression in UTUC patients by immunohistochemistry (IHC). Subsequently, we quantitatively combined the results with those from the published literature in a meta-analysis after searching several data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Ki-67 expression has been reported previously in 53 to 88% of UTUC [8,10,11,26,27]. In our study, we observed positive Ki-67 expression in 69.7% of cases.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Ki-67 expression has been reported previously in 53 to 88% of UTUC [8,10,11,26,27]. In our study, we observed positive Ki-67 expression in 69.7% of cases.…”
Section: Discussionsupporting
confidence: 78%
“…The immunostaining was assessed semi-quantitatively by considering the percentage of positive cells and staining intensity as described previously [8,18]. Ki-67 expression was classified as low (≤ 20% of cell nuclei stained positive for Ki-67), high (> 20%), and negative (0%) [10].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate data will be adopted when the available results emerge. (2) If HRs and their variance were not reported, we performed a calculation from the survival comparison statistics and its variance, which has less reliability than direct data [50][51][52]. In addition, because of the differences in the diagnostic criteria for urinary cytology among different countries and regions, the quality of this study would have been improved by standardized protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Some included studies did not provide available values of HR, RR or OR from multivariate analysis, so we performed calculations from the univariate data and compared them through formula calculations. The statistical methods we used cannot replace all the research methods, and the conclusions we obtained without correlation are limited to the scope of our research, which may have some statistical errors [63,64]. Second, we only focused on researching patients who regularly consumed aspirin.…”
Section: Discussionmentioning
confidence: 99%